Vikings. Season 1 [videorecording (Blu-Ray)] - Winnick, Katheryn; Gilsig, Jessalyn, 1971-; Standen, Clive; Byrne, Gabriel, 1950-; Fimmel, Travis, 1979-; Skarsgård, Gustaf; O'Toole, Nathan ([publisher not identified], 2013)
Journey into a thrilling ancient world in this epic new series about history's bravest and most brutally fearsome warriors; Vikings. Ragnar, a would-be Viking chieftain, longs to fulfill his destiny as an explorer and conqueror, alongside his ambitious brother Rollo and loyal wife Lagertha. But as Ragnar leads daring raids in distant realms across the ocean, treacherous forces in his Norse homeland conspire against him.